The Interaction Force between Scheelite and Scheelite/Fluorite/Calcite Measured Using Atomic Force Microscopy - Junyan Yang; Shen Qi; Bo Song; Qi Zheng; Xiaokui Che; Lijun Wang (Journal of Chemistry)
The mechanism of the formation of the hydrophobic agglomerate in fine scheelite flotation was studied using zeta potential measurement, contact angle measurement, optical microscope measurement, and atomic force microscopy (AFM) colloid probe technology. Zeta potential measurement results confirmed the adsorption of sodium oleate on scheelite, fluorite, and calcite surface and surface potential difference at different pH values of ultrapure water. Contact angle measurement results confirmed the surface of nature scheelite, fluorite, and calcite was hydrophilic, and the surface after thread by sodium oleate solution was hydrophobic. The optical microscope measurement results confirmed the agglomerates could really form in ultrapure water of pH 8 or 10 and in 1 mM sodium oleate solution of pH 10. The agglomerations were empty and not tight in ultrapure water. On the contrary, the hydrophobic agglomerations were larger and denser after treated with sodium oleate solution than that of in ultrapure water. According to the AFM experiment results, the interaction forces on hydrophilic scheelite-scheelite and scheelite-fluorite were repulsive at pH 5.6 and attractive at pH 8 or 10. However, the interaction forces on hydrophilic scheelite-calcite were attractive at pH 5.6, 8 or 10. The interaction forces on hydrophobic scheelite-scheelite, scheelite-fluorite, and scheelite-calcite were attractive strongly due to the existence of hydrophobic force. The measurement results of the interaction forces were in good agreement with the changes of zeta potential and contact angle at different conditions. The combined results could be beneficial to understand the interaction force in fine scheelite flotation.